Robust Heat Shock Response in Chlamydia Lacking a Typical Heat Shock Sigma Factor - Huang, Yehong; Wurihan, Wurihan; Lu, Bin; Zou, Yi; Wang, Yuxuan; Weldon, Korri; Fondell, Joseph D.; Lai, Zhao; Wu, Xiang; Fan, Huizhou (Frontiers in Microbiology, 2022)
Cells reprogram their transcriptome in response to stress such as heat shock. In free-living bacteria, the transcriptomic reprogramming is mediated by increased DNA-binding activity of heat shock sigma factors and activation of genes normally repressed by heat-induced transcription factors. In this study, we performed transcriptomic analyses to investigate heat shock response in the obligate intracellular bacterium Chlamydia trachomatis, which encodes only three sigma factors and a single heat-induced transcription factor. Nearly one-third of C. trachomatis genes showed statistically significant (≥ 1.5-fold) expression changes 30 min after shifting from 37 ºC to 45 ºC. Notably, chromosomal genes encoding chaperones, energy metabolism enzymes, type III secretion proteins, as well as most plasmid-encoded genes, were differentially upregulated. By contrast, genes with functions in protein synthesis were disproportionately downregulated. These findings suggest that facilitating protein folding, increasing energy production, manipulating host activities, upregulating plasmid-encoded gene expression, and decreasing general protein synthesis helps facilitate C. trachomatis survival under stress. In addition to relieving negative regulation by the heat-inducible transcriptional repressor HrcA, heat shock upregulated the chlamydial primary sigma factor σ66 and an alternative sigma factor σ28. Interestingly, we show for the first time that heat shock downregulates the other alternative sigma factor σ54 in a bacterium. Downregulation of σ54 was accompanied by increased expression of the σ54 RNA polymerase activator atoC, thus suggesting a unique regulatory mechanism for reestablishing normal expression of select σ54 target genes. Taken together, our findings reveal that C. trachomatis utilizes multiple novel survival strategies to cope with environmental stress and even to replicate. Future strategies that can specifically target and disrupt Chlamydia’s heat shock response will likely be of therapeutic value.